Pengaruh Informasi Akuntansi Terhadap Keputusan Pemberian Kredit Pada PT. Bank Rakyat Indonesia (Persero) Cabang Rantauprapat - Syahrijal Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
Credit facilities provided by banks are the biggest assets for banks. The risk of loss is largely sourced from credit activities so that if not managed properly and accompanied by adequate supervision will threaten the survival of the bank. the bank must have confidence in the prospective debtor that the funds provided will be used in accordance with the objectives, and in the end, will be returned again to the bank in accordance with the agreed agreement. The approach in this research is a quantitative approach, a data collection technique by means of a questionnaire that is by distributing a list of questions to the object under study in this case employees who channel credit granting, Documentation Studies are forms of secondary data collection, observation, and interviews. Current ratio research results affect the decision of granting credit at PT. Bank Rakyat Indonesia (Persero) Branch Rantauprapat, which is based on calculations that the current ratio has t-count greater than the table. Return on equity affects the lending decision at PT. Bank Rakyat Indonesia (Persero) Branch Rantauprapat, which is based on calculations that the return on equity has t-value greater than the table.